The give and take of social support in professional athlete career pathways - Thomas, P. G.; Walter, S.; Lucas, P.; Oldham, A. R. H. (Journal of Sports Sciences, 2026)
This article explores the dynamics of social support in emerging professional athlete career transitions. Drawing on a pragmatic research paradigm and using qualitative, instrumental multi-case methodology, the article investigates how social support shapes athlete experiences. Through in-depth accounts and reflexive thematic analysis across four cases: Boxing, Rugby League, Basketball pathways, and an independent practitioner case, the article examines the realities faced by athletes, including those who migrate internationally. Central to the inquiry are questions about the attributes that facilitate or hinder dyadic support relationships, and how practical organisational and relational support can foster both personal and athletic development in and beyond sport. By integrating existential perspectives, particularly concepts of isolation, authenticity and meaning, the research findings highlight the tension athletes, parents, coaches, and practitioners experience when bending to institutional roles and external pressures. Findings reveal that the most impactful support relationships are found not in the fulfilment of transitory or functional roles, but in connection and authenticity through genuine care, trust, presence, mutual benefit, and recognition of each other`s needs. The article positions anxiety as an everyday concern in an athlete`s life. As such, the support-provider`s responsibility is to guide emerging athletes through struggles with truth and transparency, strengthening their autonomy, skills, and resilience to thrive in sport and life. This article proposes targeted recommendations relating to developmental support environments offering insights for sports personnel and athletes.